Potential Predictability of the Spring Bloom in the Southern Ocean Sea Ice Zone: data and analysis scripts - Buchovecky, Ben; MacGilchrist, Graeme; Bushuk, Mitchell; Haumann, Alex; Frölicher, Thomas; Le Grix, Natacha; Dunne, John (Zenodo, 2023)
This repository contains the datasets and notebooks necessary to reproduce the figures in Buchovecky et al. "Potential Predictability of the Spring Bloom in the Southern Ocean Sea Ice Zone". All notebooks, except those deriving quantities from the raw model data,should work "out-of-the-box" after the appropriate local path has been set to the data.